Naval metals from mid 18th- to early 19th-century European shipwrecks: a first analytical approach - Ciarlo, Nicolás Carlos (2015)
This article gives the preliminary results of a study of metal artefacts recovered from European shipwrecks dating from the mid 18th- to early 19th-century. The analytical approach included optical emission spectrometry (OES), atomic absorption spectrometry (AAS) and infrared spectroscopy (IR) which determined the main constituents and trace element contents of the materials. Based on the latter, andother sources of information, a technological assessment was performed. Such data provides information on the functionality of artefacts, the quality of the alloys and their possible provenance.